Peran Keunggulan Kompetitif Inovasi Produk dan Jaringan Bisnis Pada Kinerja Ekonomi Desa Bobojong Manggu : Penelitian Pada UMKM Sugar Souvenir - Resya Dwi Marselina; Ahmad Hardiansyah; Ena Srilusyana; Rizky Syaifullah; Shapdani Anggara Priyadi; Tika Kartika Rahman (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The aim of this research is to determine the role of competitive advantage, product innovation, and the UMKM Sugar Souvenir business network on the economic performance of the Bobojong Manggu village. The data collection techniques used were direct observation and interviews. The research method used is descriptive qualitative, namely by collecting, processing, presenting and describing data obtained directly from observations of the research site and the results of interviews so as to obtain actual information and make it easier for readers to understand the contents of this research. The results of the research that has been carried out can be concluded that UMKM Sugar Souvenir have a quite large role in the economy of the Bobojong Manggu village. By seeing the potential of the local community who has the basics and abilities in the field of sewing, UMKM Sugar Souvenir recruited them with the aim of minimizing unemployment. This UMKM product innovation was also able to make the village cleaner because the existing plastic waste was used and recycled to make a product.